The importance of racial tolerance for anti-racism. Issue 1 (2nd January 2016) - Balint, Peter
ABSTRACT: Tolerance has an ambiguous role in anti-racism strategies. On the one hand, it is a clear antidote to racial intolerance. Yet on the other, not only is it not the only antidote to racial intolerance (respect for difference and indifference to difference are also possibilities), but the fact that it involves a negative attitude or belief and the power to act on it suggests it is far from ideal. These problems are compounded by the fact that racial tolerance can only deal with racial intolerance, which because of its intentionality seems to be only a small part of racism. In this paper, I defend racial tolerance by arguing that conceptually it does have a role in anti-racism strategies and normatively describes an important minimum for those at risk of committing acts of racial intolerance.